Market Access, Well-being, and Nutrition: Evidence from Ethiopia. (February 2017) - Stifel, David; Minten, Bart
Highlights: This is a study of market access in a rural area in northwestern Ethiopia. Relationship between household well-being, nutrition, and market access is analyzed. Remote households consume less, are more food insecure, and have less diverse diets. No statistical relationship between market access and maternal and child nutrition outcomes. Agricultural production and terms of trade differences account for differences in wellbeing. Summary: We use a unique data source from a rural area in northwestern Ethiopia to analyze the relationship between household/individual well-being, nutrition, and market access. We find that households residing in relatively more remote areas consume substantially less than households nearer to the market, they are more food insecure, and their school enrollment rates are lower. Although their diets are also less diverse, we find no significant differences in mother and child anthropometric measures. Part of the differences in well-being that we do observe can be attributed to lower household agricultural production in remote areas. Nonetheless agricultural production differences alone do not account for all the differences in household consumption levels for remote households. An additional contributing factor is the terms of trade for remote households that negatively affect both the size of the agricultural surplus that these households market and the quantity of food items that they purchase. Reducing transaction costs for remote households and facilitating migration could help equalize well-being among more or less favored locations.